Agency law and odious debts. Issue 1 (1st January 2017) - Dimitriu, Cristian
ABSTRACT: Because of the way that the international lending system works, poor nations have been forced to repay sovereign debts without having a moral obligation to do so. Suppose a corrupt public official borrows money from an international agency, or from private investors, and later on embezzles this money, or uses it to oppress the population. Suppose, further, that the lender is aware of the potential of this situation and still lends. Typically, the international community considers that successor governments have the obligation to repay the funds and the interests associated to them. In fact, this is what they usually end up doing. Public officials are all aware that if they do not honour sovereign debts, they will face all kinds of negative consequences, including exclusion from future markets, loss of reputation and legal sanctions. Owing to this mechanism, entire generations have been burdened with debts fraudulently incurred in their name by governments in the past. These kinds of debts have been known in the legal literature as 'odious'. In this article, I discuss the conditions defining the bindingness of a debt. I suggest that they can be made explicit by looking at the rules under which the lending system works at the domestic level, and by then extending these rules to the international domain. I argue that, because of their plausibility, these are the rules that should govern international lending from now on. I also discuss the feasibility of extending these rules globally, and consider potential objections to my proposal.